The Effectiveness of Flexible Ureterorenoscopy for Opaque and Non-opaque Renal Stones - Tanik, Serhat; Zengin, Kursad; Albayrak, Sebahattin; Atar, Muhittin; Imamoglu, Muhammed Abdurrahim; Bakirtas, Hasan; Gurdal, Mesut (Urology Journal, 2015)
Abstract Purpose: To evaluate the treatment success rate of flexible ureterorenoscopy (URS) for opaque and non-opaque renal stones. Materials and Methods: Ninety-four patients, who underwent flexible URS for renal stones between October 2012 and January 2014, were included. The patients were divided into two groups according to stone radiolucency. The patients were evaluated with preoperative and postoperative (at the weeks 4) computed tomography. Success of the treatment was defined as stone-free status and residual fragments < 4 mm. Results: Success of the treatment was observed in 79 (84%) patients. Sex, stone size, and stone location were factors affecting treatment success. Seventy-five (79.8%) patients had opaque stones, and 19 (20.2%) had non-opaque stones. The treatment success rates for opaque and non-opaque stones were 86.6% and 73.6%, respectively (P = .167). Flexible URS was a successful modality with acceptable morbidity to treat renal stones. Conclusion: These results show that radiolucent and opaque stones can be effectively treated by flexible URS.